2007
DOI: 10.1097/mpg.0b013e31814c3d79
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pattern of Celiac Disease Is Still Changing

Abstract: The clinical presentation of celiac disease in children changed in the last decades of the 20th century. To ascertain whether changes are still in progress, we analyzed symptoms at presentation and age at diagnosis in 307 children receiving diagnoses of celiac disease for the past 20 years. The prevalence of typical forms of celiac disease decreased in the past decade, particularly in the past 5 years (from 76% in 1987-1990 to 44%, P < 0.0001). Age at diagnosis (5.9 y, P = 0.01) and silent forms (10.6%, P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 9 publications
10
58
2
8
Order By: Relevance
“…13,14,27 On the other hand, there are some publications reported that atypical form is more frequent. 28,29 Some individuals with CD may present with anemia. Anemia usually occurs due to impaired absorption of iron, foliate, and vitamin B12 caused by mucosal damage.…”
mentioning
confidence: 99%
“…13,14,27 On the other hand, there are some publications reported that atypical form is more frequent. 28,29 Some individuals with CD may present with anemia. Anemia usually occurs due to impaired absorption of iron, foliate, and vitamin B12 caused by mucosal damage.…”
mentioning
confidence: 99%
“…CD's high prevalence, its associated comorbidities in the short and long term, and the fact that an effective treatment is available mean that the disease is a good candidate for a screening program (4,14). Screening would not only detect "subclinical" CD patients but also atypical patients who are difficult to diagnose because of their nonspecific symptoms (15)(16)(17). Despite this, previous studies have argued against screening for CD because "asymptomatic" patients may not adhere to a gluten-free diet (18).…”
Section: Analysis Of the Diagnostic Validity Of The Point-of-care Tesmentioning
confidence: 99%
“…For example there was a decrease in diarrheal manifestations, both in adult and pediatric studies, preceding the use of these CD serological markers (Rampertab 2006, Garampazzi 2007.…”
Section: Symptoms At Presentationmentioning
confidence: 99%